Agricultural Wastewater Treatment Using Coal, Coconut Fibre, Citronella And Clay As A Biofiltration - Trisshnee Thrishu, Chanthra Mokan; Mohammad Adam, Adman; Kan, Kah Hoong; Lim, Fang Lee; Nor Aslina, Abd Jalil (UIB, 2023)
River water quality has decreased due to agriculture wastewater discharge. Statistic data in 2021 showed 22.6 thousand of water pollution cases were reported in Malaysia, which is a critical issue to the aquatic plants and animals. Thus, this paper aims to measure removal efficiency of a natural and economically designed bio-filter. The bio-filter was made of coal, coconut fibre, citronella, and clay to treat agricultural wastewater and compared the water quality before and after filtering. Selected parameters (TSS, BOD, COD, and NH3-N) were assessed in the wastewater samples before and after the operation of a bio-filter on a laboratory scale. The result shows that bio-filter success to improve the agriculture wastewater quality. Consequently, we recommend that this bio-filter can be further tested on a larger scale and potentially used in the agriculture wastewater industries.